2021
DOI: 10.47191/jefms/v4-i9-06
|View full text |Cite
|
Sign up to set email alerts
|

Progressing Organisational Behaviour towards a New Normal

Abstract: The economic and social impacts of the coronavirus pandemic have affected organisations and businesses in multiple ways. The lockdown restrictions implemented by governing bodies, have resulted in organisations changing their behaviours from conventional methods of face-to-face engagement in physical settings, onto digital platforms. This study aims to identify the challenges pertaining to organisational behaviour during the covid-19 pandemic. Recommendations are made to facilitate organisations to implement c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The stigma attached to mental health is gradually decreasing within society as mental health awareness has increased within educational institutions and organisations [15]. Employees feel more comfortable to discuss their mental health concerns with trusted colleagues and peers, highlighting the openness from employees to seek help and treatment options.…”
Section: Resultsmentioning
confidence: 99%
“…The stigma attached to mental health is gradually decreasing within society as mental health awareness has increased within educational institutions and organisations [15]. Employees feel more comfortable to discuss their mental health concerns with trusted colleagues and peers, highlighting the openness from employees to seek help and treatment options.…”
Section: Resultsmentioning
confidence: 99%
“…The pandemic has deeply affected the work environment in organizations as the fear of uncertainty and anxiety prevails among employees, and poor leadership can lead to employee retaliation (Kakarika et al, 2022). Theoretical research by Somani (2021) has suggested incorporating behavior changes to increase employee engagement. Delibasic et al (2021) explored the observed trends in employee behavior and work performance that are causing a change in organizational behavior in the context of the motivation, ability, role perceptions, and situational factors (MARS) model.…”
Section: Positive Organizational Behaviourmentioning
confidence: 99%